IoT based data acquisition and remote monitoring system for large-scale photovoltaic power plants - KALAY, MUHAMMET ŞAMİL; SAĞLAM, ŞAFAK; ORAL, BÜLENT (My University, 2022)
Normal 0 21 false false false DE X-NONE AR-SA /* Style Definitions */ table.MsoNormalTable {mso-style-name:\"Table Normal\"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:\"; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; line-height:12.0pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:\"Times New Roman\",serif; mso-ansi-language:EN-US; mso-fareast-language:EN-US;} The amount of solar capacity deployed worldwide has doubled in the past decades. The increasing use of solar energy makes photovoltaic (PV) power plants substantial. In PV power plants, reducing maintenance and operating costs positively affects efficiency. A failure in any module can reduce or interrupt the production of electrical energy, causing significant losses in both efficiency and revenue. Therefore, responding to a fault as quickly as possible in PV power plants is critical. The ability of the PV plant operator to react to potential faults is directly related to the rapid detection of faulty modules. In this paper, IoT based data acquisition and monitoring system is designed to diagnose module failures and remotely monitor for PV power plant\"s performance. The current, voltage, module surface temperature, and solar radiation values are measured for each PV module. These data are transmitted wirelessly to long distances with LoRa modules. All data acquired in the central recording unit device are transferred to the internet, enabling online access and also stored on the memory card.
Keywords: Elektrik-Elektronik Mühendisliği; Enerji; Yenilenebilir Enerji; Mühendislik ve Teknoloji; Electrical and Electronics Engineering; Energy; Renewable energy; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, ELEKTRİK VE ELEKTRONİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, ELECTRICAL & ELECTRONIC; ENERGY & FUELS; Enerji Mühendisliği ve Güç Teknolojisi; Yenilenebilir Enerji, Sürdürülebilirlik ve Çevre; Sinyal İşleme; Genel Enerji; Elektrik ve Elektronik Mühendisliği; Yakıt Teknolojisi; Enerji (çeşitli); Fizik Bilimleri; Energy Engineering and Power Technology; Renewable Energy, Sustainability and the Environment; Signal Processing; General Energy; Electrical and Electronic Engineering; Fuel Technology; Energy (miscellaneous); Physical Sciences